Efforts to involve youth in policy making in Egypt post-2014 - Hesham, Mohamed (AUC Knowledge Fountain, 2019)
Egypt has a large youth population; youth between 18 - 29 years represent one fifth of the population. Egypt has long faced challenges adopting serious national policies for youth inclusion and participation. There has been an absence of political commitment towards preparing youth for leadership in addition to promoting youth engagement in policy making. Reviewing youth participation literature reveals that the absence of such strategy can potentially contribute to social and political unrest in the society. Following the announcement of the year of youth in 2016 by the current political leadership, there were a number of initiatives and activities to engage youth in public discussions. These efforts involved the initiation of governmental leadership programs,such as the Presidential Leadership Program, National Youth Conferences and the establishment of the National Academy for Youth Training and Empowerment. This study aims at understanding the recent governmental efforts in promoting youth inclusion and participation in public policy making. The study follows a qualitative methodology through conducting in-depth interviews with field professionals, in addition to desk review that draws on the guidelines of youth involvement. Interviews were conducted with representatives from the National Specialized Councils, National Academy for Youth Training and Empowerment, in addition to young men and women who participated in governmental youth initiatives and are currently working in public leadership positions. Moreover, interviews were held with civil society representatives and youth volunteers in National Youth Conferences who shared their insights on the issue of youth participation in public policies and decision-making in Egypt. The analysis shows noticeable progress in the youth preparation for participation starting from 2016 in addition to governmental progress in raising the percentages of female participants in decision and policy making processes. The analysis shows that the establishment of the National Academy for Youth Training and Empowerment as an independent institution is a promising indicator for the state commitment towards youth. However, there is a need to expand the youth representation in these initiatives through empowering civil society organizations and maintaining a comprehensive set of policies to ensure the sustainability and effectiveness of these efforts and the re-establishment of trust between youth and the government.